Anti-allodynic and antihyperalgesic effects of zerumbone through involvement of monoaminergic pathways in mice model of neuropathic pain - Chia, Jasmine Siew Min (2018)
Neuropathic pain is a pain condition that arises following an injury to the nervous system, persisting past the presence of any noxious stimulus or inflammation. The complex and multifaceted mechanisms underlying the development of neuropathic pain is yet to be fully understood. For this reason, treatments available for neuropathic pain patients are not specific and do not provide sufficient pain relief. Zerumbone is the major bioactive compound found in rhizomes of the Zingiber zerumbet (L.) Smith ginger plant. Zerumbone has shown to possess multiple pharmacological potentials, most importantly in exhibiting anti-allodynic and antihyperalgesic effects in a neuropathic pain animal model. Therefore, the present study was conducted to explore the mechanisms – mainly the inhibitory monoaminergic system, in the antineuropathic properties of zerumbone in a chronic constriction injury (CCI)-induced neuropathic pain mice model. The chronic constriction injury model on the sciatic nerve was employed in ICR male mice to develop neuropathic pain. The determination of the effective dosage of zerumbone in exhibiting its anti-allodynic and antihyperalgesic effects were conducted by intraperitoneal administration of zerumbone at 5, 10 and 50 mg/kg on Day 14 following CCI surgery. Behavioural responses were assessed using the von Frey filament test (mechanical allodynia) and Hargreaves plantar test (thermal hyperalgesia). Zerumbone at 10 mg/kg exhibited significant anti-allodynic and antihyperalgesic effects in the CCI neuropathic pain mice. The monoaminergic system is mainly controlled by serotonergic and noradrenergic projections and receptors. Investigation into the involvement of the serotonergic system was conducted by firstly depleting serotonin levels using ρ-chlorophenylalanine (PCPA), whereby zerumbone’s antineuropathic properties were significantly reversed in both von Frey filament and Hargreaves plantar tests. Following this, pre-administration of specific 5-HT receptor subtype antagonists prior to zerumbone (10 mg/kg) treatment significantly indicated the involvement of 5-HT receptor subtypes 1A, 1B, 2A, 3, 6 and 7. Further investigation revealed an increase in 5-HT1A receptor expression in mice brain samples following zerumbone treatment in CCI-induced neuropathic pain mice, analysed using Western Blot. Following this, the involvement of the noradrenergic system was initially investigated by administering non-specific α- and β-adrenergic receptor antagonists prior to zerumbone. Further investigation into specific adrenergic receptor subtypes revealed that mainly α1-, α2- and β2-adrenergic receptors are necessary for zerumbone to exhibit its antineuropathic properties. The decrease in α2A-adrenergic receptor expression suggests the inhibitory action of zerumbone against the upregulation of these receptors following nerve injury, which has shown to facilitate nociceptive transmission. To look further into the mechanisms of action of zerumbone, prominent receptors and systems involved in the pain pathway that are known to enhance the inhibitory tone of the monoaminergic system were elucidated. The findings demonstrated the involvement of TRPV, NMDA, cannabinoid CB1 and PPARα, PPARγ receptors in zerumbone exhibiting its antiallodynic and antihyperalgesic effects in neuropathic pain conditions. Moreover, expression of TRPV1 and NMDA NR2B receptors increased following zerumbone treatment. Data were analysed using One-way Analysis of Variance (ANOVA) followed by Tukey’s post hoc test, with the level of significance set at p<0.05. In conclusion, the current study elucidated the involvement of the monoaminergic – serotonergic and noradrenergic, vanilloid, glutamatergic, cannabinoid and nuclear hormone receptor systems in zerumbone’s antineuropathic properties.